1992
DOI: 10.1007/bf02389636
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immunization by husband's leukocytes for repeated fetal death associated with mild pre-eclampsia — case report with successful outcome

Abstract: We report a case of repeated fetal death at 31 gestational weeks associated with mild non-proteinuric pre-eclampsia and intrauterine growth retardation. After double intradermal immunisation with paternal leukocytes, a third pregnancy proceeded uneventfully until it ended at 38 weeks. Maternal anti-paternal blocking antibody activity was assessed by the erythrocyte antibody inhibition (EAI) test. Serologic testing revealed that the couple did not share HLA class I antigens. The mechanisms underlying the likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…36,49,50 There has been also a report of a successful maternal immunization by husband's leukocytes for repeated fetal death associated with preeclampsia. 37 Indeed, immunization can produce larger babies, both in humans and in abortion-prone mice, and in the latter, direct measurements of placental weight and thickness have suggested improved growth. 38,39 It is our hypothesis that this improved growth may be a result of, in part, a better blood supply occasioned by suppression of fgl2 expression.…”
Section: Expression Of Fgl2 Mrna and Protein In Human Pregnancy Tissuementioning
confidence: 99%
“…36,49,50 There has been also a report of a successful maternal immunization by husband's leukocytes for repeated fetal death associated with preeclampsia. 37 Indeed, immunization can produce larger babies, both in humans and in abortion-prone mice, and in the latter, direct measurements of placental weight and thickness have suggested improved growth. 38,39 It is our hypothesis that this improved growth may be a result of, in part, a better blood supply occasioned by suppression of fgl2 expression.…”
Section: Expression Of Fgl2 Mrna and Protein In Human Pregnancy Tissuementioning
confidence: 99%
“…But placebo treatment of recurrent abortion has also been demonstrated to be successful in about 60% of cases. Concerning immunotherapy and the prevention of preeclampsia STECK et al [116] reported a case of repeated fetal death associated with preeclampsia and fetal growth retardation. After double intradermal immunization with paternal leucocytes, a third pregnancy proceeded uneventfully.…”
Section: Immunotherapymentioning
confidence: 99%